Understanding the Mechanisms of Parental Divorce Effects on Child's Higher Education - Yen-Chien Chen; Elliott Fan; Jin-Tan Liu (Institute of Labor Economics (IZA), 2021)
We combine multiple administrative datasets from Taiwan to evaluate the degree to which the adverse divorce effect on the child's higher education operates through deprivation of economic resources. Using one million siblings, we find that parental divorce occurring at ages 13-18 significantly decreased the likelihood of university admission at age 18. Among the same siblings, we find that those who experienced parental job loss (due to firm closure) occurring at the same ages did not suffer a declined likelihood of university admission, although parental job loss led to a significant and persistent reduction in family income. After carefully examining the compatibility of the parental divorce effect and parental job-loss effect, we conclude that reduced income is unlikely a major mechanism delivering the parental divorce effect. Further examinations show that boys and girls are equally susceptible, and younger teenagers are more susceptible than the more mature ones, to parental divorce.
Keywords: I20; J12; J64; 330; parental divorce; parental job loss; college admission